Μελέτη των φαινομένων ενίσχυσης της οπτικής παγίδευσης λόγω διέγερσης πλασμονικού πεδίου - Δαλάκα, Ελένη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών. Τομέας Φυσικής, 2015)
Optical tweezers are important tools which nd many applications in fields such as medicine, biology, microelectronics and even industry. The phenomenon of optical trapping is based on phenomena of pressure of radiation and it constitutes of the immobilization of a particle, with size in the order of micrometers (mm), when this particle is situated under the in fluence of a laser beam. However, the size limitation of the trapped particle in the optical trapping gave rise to the need of (made us introduce) introducing the phenomenon of plasmonics in the optical tweezers problem. Plasmonics are the quantums of plasma oscillations and it is well known that their excitation can strengthen the electromagnetic eld locally, giving the possibillity of trapping smaller particles, under the Rayleigh limitation. In this thesis, we tried to determine,using computational simulations, which metallic nanostructure is able to increase the local electric eld at a maximum. The computation of the increase in the electric eld, has been made through the calcualtion of the total optical force on the surface of the particle, for di fferent metallic nanostructures. Firstly, we made a short reference to the phenomena of optical tweezers and plasmonics in two di fferent chapters (Chapter 2 and Chapter 3 respectively), explaining the phenomena and the meanings that are used, in the fol- lowing chapters of this thesis. In the chapter 4 the results of the three-dimensional simulations are analyzed, while there is a reference to the two-dimensional simu- lations as well. In addition, in chapter 5, we refer to the results obtained, using the computational method of simulation FDTD, and the experimental measure- ments from the convetional optical trapping experiment, follow (Chapter 6). These experiments have been conducted in the laboratory of Laser Development and Ap- plications in the Physics Department, in the School of Mathematical and Phyisical Sciences. In the conclusion of this thesis, there are some suggestions for future re- search, in theoritical and experimental basis, as well as some improvements of the computational models.